Triggering cell death in cancers using self-illuminating nanocomposites - Rajh, Tijana; Koritarov, Tamara; Blaiszik, Ben; Rizvi, Syeda Fatima Z.; Konda, Vani; Bissonnette, Marc (Frontiers in Chemistry, 2022)
Bioinspired photocatalysis has resulted in efficient solutions for many areas of science and technology spanning from solar cells to medicine. Here we show a new bioinspired semiconductor nanocomposite (nanoTiO2-DOPA-luciferase, TiDoL) capable of converting light energy within cancerous tissues into chemical species that are highly disruptive to cell metabolism and lead to cell death. This localized activity of semiconductor nanocomposites is triggered by cancer-generated activators. Adenosine triphosphate (ATP) is produced in excess in cancer tissues only and activates nearby immobilized TiDoL composites, thereby eliminating its off-target toxicity. The interaction of TiDoL with cancerous cells was probed in situ and in real-time to establish a detailed mechanism of nanoparticle activation, triggering of the apoptotic signaling cascade, and finally, cancer cell death. Activation of TiDoL with non-cancerous cells did not result in cell toxicity. Exploring the activation of antibody-targeted semiconductor conjugates using ATP is a step toward a universal approach to single-cell-targeted medical therapies with more precision, efficacy, and potentially fewer side effects.